The role of stress mindset in shaping cognitive, emotional, and physiological responses to challenging and threatening stress - Crum, Alia J.; Akinola, Modupe; Martin, Ashley; Fath, Sean (Anxiety, stress, and coping, 2017)
Background and objectives: Prior research suggests that altering situation-specific evaluations of stress as challenging versus threatening can improve responses to stress. The aim of the current study was to explore whether cognitive, physiological and affective stress responses can be altered independent of situation-specific evaluations by changing individuals' mindsets about the nature of stress in general. Design: Using a 2 × 2 design, we experimentally manipulated stress mindset using multi-media film clips orienting participants (N = 113) to either the enhancing or debilitating nature of stress. We also manipulated challenge and threat evaluations by providing positive or negative feedback to participants during a social stress test. Results: Results revealed that under both threat and challenge stress evaluations, a stress-is-enhancing mindset produced sharper increases in anabolic ("growth") hormones relative to a stress-is-debilitating mindset. Furthermore, when the stress was evaluated as a challenge, a stress-is-enhancing mindset produced sharper increases in positive affect, heightened attentional bias towards positive stimuli, and greater cognitive flexibility, whereas a stress-is-debilitating mindset produced worse cognitive and affective outcomes. Conclusions: These findings advance stress management theory and practice by demonstrating that a short manipulation designed to generate a stress-is-enhancing mindset can improve responses to both challenging and threatening stress.